Elaboración de un software educativo como material de apoyo didáctico en el desarrollo del proceso enseñanza- aprendizaje para la asignatura de estudios sociales en el 8vo año de educación general básica del colegio nacional San Pedro de Vilcabamba, periodo 2012-2013 - Alvarado León, Carmen Delia (2014)
Research: Development of educational software as a support for the development of the teaching-learning process in the subject of Social Studies, Colegio San Pedro de Vilcabamba, the difficulty of understanding students misinformation and training of teachers is evident in terms of educational technological material The thesis project was conducted in the vicinity of the southern region of the province of Loja, the same which has 16 cantons is the one that bears his name, which is structured urban and rural parishes, among these is San Pedro de Vilcabamba, located south of the city where this activity was accomplished. Scientific, deductive, inductive, synthetic and descriptive: To achieve the objectives, the use of methods was necessary. Besides the techniques of observation, interviews, surveys, evaluation form for teachers and students, who contributed valid, reliable and relevant information to solve the problem posed. Once the investigative process concluded Educational Software favor improving teaching practice and meaningful learning of making them students as material pedagogical support and will contribute to motivate students to make critical, participatory while proactive is design.